Egg Production in Poultry Farming Is Improved by Probiotic Bacteria - Peralta-Sánchez, Juan Manuel; Martín-Platero, Antonio Manuel; Ariza-Romero, Juan José; Rabelo-Ruiz, Miguel; Zurita-González, María Jesús; Baños, Alberto; Rodríguez-Ruano, Sonia María; Maqueda, Mercedes; Valdivia, Eva; Martínez-Bueno, Manuel (Frontiers in Microbiology, 2019)
Antimicrobial resistance (AMR) is one of the most serious threats for human health in the near future. Livestock has played an important role in the appearance of antibiotic-resistant bacteria, intestinal dysbiosis in farming animals, or the spread of AMR among pathogenic bacteria of human concern. The development of alternatives like probiotics is focused on maintaining or improving production levels while diminishing these negative effects of antibiotics. To this end, we supplied the potential probiotic Enterococcus faecalisUGRA10in the diet of laying hens at a final concentration of 108 Colony Forming Units per gram (CFU/g) of fodder. Its effects have been analyzed by: i) investigating the response of the ileum and caecum microbiome; and ii) analyzing the outcome on eggs production. During the second half of the experimental period (40 to 76 days), hens fed E. faecalis UGRA10 maintained egg production, while control animals dropped egg production. Supplementation diet with E. faecalis UGRA10 significantly increased ileum and caecum bacterial diversity (higher bacterial richness and Faith’s diversity index) of laying hens, with animals fed the same diet showing a higher similarity in microbial composition. These results point out to the beneficial effects of E. faecalis UGRA10 in egg production. Future experiments are necessary to unveil the underlying mechanisms that mediate the positive response of animals to this treatment.